2013
DOI: 10.4097/kjae.2013.64.6.524
|View full text |Cite
|
Sign up to set email alerts
|

Opioid sparing effect of low dose ketamine in patients with intravenous patient-controlled analgesia using fentanyl after lumbar spinal fusion surgery

Abstract: BackgroundThe opioid sparing effect of low dose ketamine is influenced by bolus dose, infusion rate, duration of infusion, and differences in the intensity of postoperative pain. In this study, we investigated the opioid sparing effect of low dose ketamine in patients with intravenous patient-controlled analgesia (PCA) using fentanyl after lumbar spinal fusion surgery, which can cause severe postoperative pain.MethodsSixty patients scheduled for elective lumbar spinal fusion surgery were randomly assigned to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 25 publications
2
63
2
Order By: Relevance
“…The use of ketamine infusions has been shown to be an opiate-sparing technique in managing post-operative pain following a variety of surgeries, including abdominal (Guillou et al, 2003; Webb et al, 2007; Zakine et al, 2008; Kaur et al, 2015), thoracic (Michelet et al, 2007; Nesher et al, 2008, 2009; Chazan et al, 2010), orthopedic (Adam et al, 2005; Kollender et al, 2008; Cha et al, 2012; Akhavanakbari et al, 2014), spinal (Kim et al, 2013) and gynecological (Sen et al, 2009; Suppa et al, 2012). However, others have not observed ketamine to have significant clinical benefits or opioid-sparing effects in postoperative pain management (Jensen et al, 2008; Sveticic et al, 2008; Reza et al, 2010; Yeom et al, 2012).…”
Section: Clinical Uses In Medicinementioning
confidence: 99%
“…The use of ketamine infusions has been shown to be an opiate-sparing technique in managing post-operative pain following a variety of surgeries, including abdominal (Guillou et al, 2003; Webb et al, 2007; Zakine et al, 2008; Kaur et al, 2015), thoracic (Michelet et al, 2007; Nesher et al, 2008, 2009; Chazan et al, 2010), orthopedic (Adam et al, 2005; Kollender et al, 2008; Cha et al, 2012; Akhavanakbari et al, 2014), spinal (Kim et al, 2013) and gynecological (Sen et al, 2009; Suppa et al, 2012). However, others have not observed ketamine to have significant clinical benefits or opioid-sparing effects in postoperative pain management (Jensen et al, 2008; Sveticic et al, 2008; Reza et al, 2010; Yeom et al, 2012).…”
Section: Clinical Uses In Medicinementioning
confidence: 99%
“…Thus, the objectives of this chart review investigation evaluated perioperative ketamine combined with traditional opioid-based pain management and examined narcotic rescue requirements in LDLT patients. If perioperative ketamine can be shown to improve postoperative pain and positively influence donor-patient analgesic experiences, then given the deficiencies of current analgesic options for this type of surgery, ketamine use during partial hepatectomy might prove beneficial and might improve patient outcomes (14).…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine is a non-opioid N-methyl-D-aspartate receptor antagonist and effective adjunct to opioids for improving postoperative analgesia following moderate-to-severe pain-inducing surgery (14,28). Ketamine is also associated with opioid tolerance reversal, and no medication interactions have been reported with its use (29).…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine appears to possess unique immunomodulatory and analgesic properties that effectively attenuate inflammation and reduce pain without the use of opioid/NSAID analgesics -which have become a worldwide epidemic leading to addiction, overdose, and death [15]. Moreover, our own clinical experience and published clinical studies by others [16] have found that ketamine can be an opioid-sparing option that can be used as a tool to reduce and, in some cases, discontinue chronic opioid use.…”
Section: Discussionmentioning
confidence: 99%